What are long-term benefits of weight reducing diets in adults? A systematic review of randomized controlled trials - Avenell, A; Brown, T.J; McGee, M.A; Campbell, M.K; Grant, A.M; Broom, J; Jung, R.T; Smith, W.C.S (Journal of human nutrition and dietetics, 2004)
Background  Evidence is needed for the best long‐term diet for weight loss, and improvement in cardiac risk and disease in obese adults. Methods  We systematically reviewed randomized controlled trials (RCTs) in any language. We searched 13 databases and handsearched journals. Trials lasted 1 year or more. One investigator extracted the data and a second checked data extraction. Trial quality was assessed. Results  Low fat diets (LFDs) produced significant weight losses up to 36 months (−3.55 kg; 95% CI, −4.54 to −2.55 kg). Blood pressure, lipids and fasting plasma glucose improved with these diets after 12 months. Four studies found that LFDs may prevent type 2 diabetes and reduce antihypertensive medication for up to 3 years. A very low calorie diet (VLCD, <4.2 MJ day−1) was associated with the most weight loss after 12 months (−13.40 kg; 95% CI, −18.43 to −8.37 kg) in one small study with beneficial effects on asthma. There was no evidence that low carbohydrate protein sparing modified fasts (PSMFs) were associated with greater long‐term weight loss than low calorie diets (LCDs, 4.2–6.7 MJ day−1) or VLCDs. PSMFs were, however, associated with greater lowering of fasting plasma glucose and HbA1c than LCDs. Conclusions  Little evidence supports the use of diets other than LFDs for weight reduction. With the increasing prevalence of morbid obesity, long‐term follow‐up in RCTs is needed to evaluate the effect of LCDs, VLCDs and PSMFs more fully.